Intimate Partner Violence Within the Malaysian Legal Framework - Mohammed Na'aim, Mohd Safri; Rajamanickam, Ramalinggam; Nordin, Rohaida (UUM Press, 2022)
In Malaysia, matters pertaining to domestic violence are governed by the Domestic Violence Act 1994 (DVA 1994) (Act 521). The DVA 1994 uses the term domestic violence rather than intimate partner violence (IPV). Definition of domestic violence not only describe the types of domestic violence are, it also identifies the victims of domestic violence. Those who fall under the category of domestic violence victims may seek legal protection under the DVA 1994 namely protection orders, compensation and access to a rehabilitation programmed. Unlike domestic violence, the term IPV is not defined by the DVA 1994. This may raise a question regarding the status of IPV victims on whether they are protected under the said Act. The research examines the definitions of domestic violence and IPV, how the DVA 1994 protects domestic violence victims, and to what extent legal protection is given to IPV victims. This article adopts the doctrinal legal research involving a detailed analysis of the DVA 1994, the Penal Code (Act 574), the Criminal Procedure Code (Act 593) and case law. This research found that the definition of IPV within the DVA 1994 arguably cover only spouses and former spouses, leaving other unmentioned intimate relationships such as cohabitation and dating partner outside of the application of the Act. Although not covered by the DVA 1994, if individuals in such relationships are harmed by their partners, they can lodge a police report for violation of the criminal provisions of the Penal Code for legal action to be taken.